Efektivitas Pelatihan Shalat Khusyuk dalam Menurunkan Kecemasan pada Lansia Hipertensi - Yulia Wardani; Fuad Nashori; Qurotul Uyun (JIP (Jurnal Intervensi Psikologi), 2016)
This study aimed to examine the effect of Solemn Prayer training to reduce anxiety in the elderly with hypertension and can provide peace of mind. Subjects in this study amounted to 9 elderly, who were divided into 5 experimental groups and 4 control groups. Measuring instruments used in this research is scale BAI (Beck Anxiety Scale) were given at the pre-test, post-test and follow-up. Analysis of the research is quantitative analysis using Anova Repeated Parametric Measurement to determine the level of anxiety of elderly hypertensive after the training given solemn prayer. The result of research indicates that effective fervent prayer training to reduce anxiety elderly hypertension with F = 75.075 and p = 0.00 (p <0.05). This study shows that training solemn prayer can be used as one way to reduce anxiety in elderly hypertensive.Â Keywords: Anxiety, Training Solemn Prayer, Elderly Hypertension